Analisis Kimia dan Kualitas Air Hujan di Kota Palu Sebagai Penyebab Terjadinya Hujan Asam - Alfiandy, Solih; Permana, Donaldi Sukma; Nugraha, Muharam Syam; Aulia Putri, Isna Jutika (Jurnal Riset Kimia, 2021)
Acidic compounds such as sulfur dioxide (SO2) and nitrogen oxides (NOx), which are generally emitted into the atmosphere by human activities from burning fossil fuels, motor vehicles and industry, react with water and oxygen to produce acidic rain that falls to the earth's surface. This study aims to investigate the quality of rainwater chemical compounds at the Mutiara Palu Meteorological Station using 282 samples derived from the BMKG Air Quality Database during February 1993 – January 2020. The method used are descriptive analysis and correlation analysis to determine the relationship between chemical compound reactions that occur in the rainwater in Palu City. The results showed that the chemical compounds in rainwater in Palu City were dominated by strong acid compounds in the form of Cl-, SO42-, and NO3- compounds with a percentage of 63% and the most dominant quality was in the acidic rain category with a pH value below 5.6, as much as 55.7%. Chemical compounds contained in rainwater in Palu City are mineral compounds that originated from natural form of minerals, particularly from sea salt. The relationship between chemical compounds contained in rainwater has varied values and is in the low to moderate category. In general, the results indicate that the quality of rainwater in Palu City is low and not recommended for health and the environment.